Improving Employer Attractiveness of Salon MOZ5 Bandung through Employer Branding - Zuliah, Gilari Ratna; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2016)
Abstract—Nowadays companies have to compete with  their competitors, not only on products or services, but also on attracting employees. During the last couple of years, competition concerning attracting, recruiting, and retaining the best possible skilled employees has increased significantly. Without the right applicants, organizations are not able to develop the level of competitive advantage needed to compete in an unstable economy. As a consequence of those, companies are increasingly trying to make themselves as attractive employers on the labor market. One way to attract recruits and assure the current employees are engaged in the culture and the strategy of the firm is employer branding. In salon industry like Salon Moz5 Bandung, the need for  professional employees is very important to satisfy customers.Because It affects the revenue of the salon.However, in February 2016, the revenue of Salon Moz5 Bandung decreased drastically. The capacity of the salon is not enough with the number of customers. It was because of the lack of applicants applying for jobs in the salon. One thing that can make applicants apply in a company is employer branding. It is important to know what factors attracts new employees and then make it as employer branding. The researcher is interested to analyze the effects of the location, corporate image, corporate social responsibility, task, and flexibility in working to employee attractiveness. The research is conducted to test several hypotheses which are; is there a significant effect of location, corporate image, corporate social responsibility, task, and flexibility in working to employer attractiveness and how to increase the number of applicants applying for jobs at Salon Moz5 Bandung. The analysis technique used in this research is the multiple linear regression. The respondents are 74 students of SMK N 9 Bandung majoring skin and hair care in 3rd years and alumnus who just graduated in 2016. The result of the analysis shows that the only factor that has a significant effect on employer attractiveness is corporate image. This research recommends to Salon Moz5 Bandung’s owner to make a more well known corporate image, create a brand ambassador program, and socialize about Salon Moz5 Bandung to schools so the number of applicants will increase.Keywords—location, corporate image, corporate social responsibility, task, flexibility in working, employer attractivenss, salon